2010
DOI: 10.1007/s10750-010-0379-4
|View full text |Cite
|
Sign up to set email alerts
|

Ostracods and the Holocene palaeolimnology of Lake Qarun, with special reference to past human–environment interactions in the Faiyum (Egypt)

Abstract: We present an ostracod record covering the past two millennia from an 8.25-m core taken from Lake Qarun, in the Faiyum Depression of Egypt. The occurrence of ostracod species in the lake is controlled primarily by variations in solute composition, which are in turn related to shifts in catchment land use. At times when the Faiyum Depression supported thriving agriculture, lake water contained Na ? -Cl -brine, and Cyprideis torosa dominated the ostracod assemblage. When the Faiyum Depression experienced periods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 73 publications
(108 reference statements)
0
43
0
1
Order By: Relevance
“…Alluviation, around what is now the lagoon of Ghar El Melh (Tunisia), occurred rapidly between 2400 and 1500 b2k, partly coinciding with the Punic-Roman period (Delile et al, 2015). Baioumy et al (2010) attributed lithological variations in a Lake Qarun sediment core to lake level lowering by people regulating the lake inflow around the beginning of the Common Era and Keatings et al (2010) showed that the ostracod species changed around this time.…”
Section: Africamentioning
confidence: 99%
“…Alluviation, around what is now the lagoon of Ghar El Melh (Tunisia), occurred rapidly between 2400 and 1500 b2k, partly coinciding with the Punic-Roman period (Delile et al, 2015). Baioumy et al (2010) attributed lithological variations in a Lake Qarun sediment core to lake level lowering by people regulating the lake inflow around the beginning of the Common Era and Keatings et al (2010) showed that the ostracod species changed around this time.…”
Section: Africamentioning
confidence: 99%
“…Local change can be recognized in prehistoric times, for example, deforestation around Lake Ohrid 5000 years ago (Wagner et al 2009); as a result of mining in the Tinto Estuary, Spain, in c. 1500 BC (Ruiz et al 2009); and as a result of the late Neolithic and Bronze Age occupation of Apulia, Italy (Caldara & Simone 2005). Ostracod populations from the coastal strip of Portugal, Spain and Malta and Lake Qarun, Egypt, preserve the effects of anthropogenic pollution, deforestation and agriculture from as early as Roman times (Almeida et al 2009;Keatings et al 2010;Currás et al 2012;Marriner et al 2012). By c. 1550 AD, eutrophication in parts of the Norwegian coastal zone (e.g.…”
Section: A Date For the Anthropocenementioning
confidence: 99%
“…The aims of this paper are therefore to document geomorphic processes, sedimentary environments, and sources responsible for the spatial-temporal variability of sediments within a specific region of the north shore where surface archaeological materials are abundant, and to consider the relationship between the Keatings et al, 2010).…”
Section: Introductionmentioning
confidence: 99%